Analysis of semen parameters of recovered patients after COVID-19 (Annals of Medical Research, 2023)
Aim: The COVID-19 has spread rapidly around the world. Apart from primarily targeting the lungs and causing acute respiratory distress syndrome with severe respiratory symptoms and high risk of death, the disease can also cause damage to other organs such as the heart, kidney, and testis. Studies have shown that men are more likely to get infected by the disease than women and the death rate due to the disease is found to be higher in men. We aimed to show the effects of COVID-19 on sperm parameters.Materials and Methods: In the study, semen analyzes of COVID-19 patients and healthy control groups were compared according to the presence or absence of PCR-confirmed SARS-CoV-2 positivity in hospital records. Patients with COVID-19 (+) were the patients who had mild disease. A total of 510 participants, 53 COVID-19 patients and 457 healthy control groups. After positivity confirmation of recovered COVID-19 patients using PCR, semen analysis was performed after an average of 157 (24-355) days. Also, in order to evaluate the short-term and long-term effects of the disease, patients were grouped as those with less than 90 days and more than 90 days after receiving the positive PCR result.Results: While the mean progressive motility of sperm was 41.45±(19.21) in the recovered COVID-19 patients, it was 38.35±(21.74) in the control group. The mean total motility was 55.74±(19.34) in recovered COVID-19 patients, where as it was 51.84±(22.45) in control group. The percentage of normal sperm morphology was 11.45±(5.97) in recovered COVID-19 patients, however it was 11.19±(8.08) in control group. The sperm concentration was found to be 68.60±(56.22) x 106/ml in recovered COVID-19 patients, but it was 74.10±(61.72) x 106/ml in control group. Finally, the mean sperm immobility was 44.26 ±(19.34) in recovered COVID-19 group, however it was 48.16±(22.45) in control group.Conclusion: In the study, when the semen analysis results of patients who recovered after COVID-19 and healthy control groups were compared in terms of semen parameters according to the recovery time period, no statistically significant difference was found. More studies are needed to fully understand the effects of COVID-19 on the reproductive system.
Keywords: SARS-CoV-2; COVID-19; Male fertility; Sperm; Semen parameters